2004
DOI: 10.1212/01.wnl.0000101461.61501.65
|View full text |Cite
|
Sign up to set email alerts
|

Burden of first-ever ischemic stroke in the oldest old

Abstract: The burden of ischemic stroke is high in subjects 80 years old or older, contributing about one-third of health care utilization and 59.8% of deaths within 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
80
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(100 citation statements)
references
References 17 publications
(15 reference statements)
17
80
1
1
Order By: Relevance
“…The incidence of stroke rises significantly in the presence of multiple risk factors (Marini et al., 2004). Advanced age is a leading risk factor for stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of stroke rises significantly in the presence of multiple risk factors (Marini et al., 2004). Advanced age is a leading risk factor for stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In China, there have been no such studies. Therefore, there is a urgent need to confirm the safety and efficacy of rt-PA in these patients [4,5]. The present study aimed to reveal whether rt-PA could be safely and efficiently used on Chinese patients [80 years old with acute ischemic stroke.…”
mentioning
confidence: 98%
“…A small number of studies have investigated the efficacy of rt-PA for elderly stroke patients in Japanese and Caucasian populations [4,5]. According to the American Heart Association/American Stroke Association Guidelines, patients over 80 years of age can be selected for rt-PA thrombolysis [6] and the Third International Stroke Trial found that the benefit of rt-PA did not diminish in patients older than 80 years [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although >80-yearold patients with stroke have 2-fold higher mortality and morbidity even with thrombolysis compared with ≤80-yearold patients, 2,3 pooled results of thrombolysis and neuroprotection trials suggest potential for benefit with thrombolysis in >80-year-old patients. 4 This may be important for patients wake-up ischemic stroke (WUIS), who are significantly older, constitute 14% of acute presentations, and 36% may be eligible for thrombolysis.…”
mentioning
confidence: 99%